Censorship of Translated Fiction in Nazi Germany - Sturge, Kate (TTR, 2002)
AbstractThis paper outlines the processes of censorship affecting translation under Nazi rule. Despite a markedly suspicious attitude towards translated fiction, the Nazi regime did not simply eliminate it. In fact, far from collapsing in 1933, the publication of translated fiction actually increased, both in absolute terms and as a proportion of all fiction, until the outbreak of war. However, if in purely quantitative terms translation flourished, the figures mask deep qualitative shifts: Jewish or anti-Nazi authors, translators and publishers disappeared; safe-selling genres came to dominate the market; and source-language preferences changed. These shifts were clearly the outcome of aggressive state measures, both classic “negative” censorship—the banning of literary producers and products or the imposition of “voluntary” self-regulation—and the energetic promotion of approved forms of translation. At the same time, more detailed study suggests that even for non-approved forms, the influence of state control was not always so clear-cut. In the case of the translated detective fiction of the time, censorship in translation was an amalgam of state intervention, pre-emptive filtering, selective readings of the source genre’s ambivalences, and the “normal” pressures of the book market. Even in this totalitarian context of extreme literary control, it remains difficult to define the borders of “translation censorship” as such.